Don't fear the (small) bite: A narrative review of the rationale and misconceptions surrounding closure of abdominal wall incisions - Theodorou, Alexis; Banysch, Mark; Gök, Hakan; Deerenberg, Eva B.; Kalff, Joerg C.; von Websky, Martin W. (Frontiers in Surgery, 2022)
Background: The most common complications related to the closure of abdominal wall incisions are surgical site infections, wound dehiscence and the development of an incisional hernia. Several factors relating to the surgical technique and the materials used have been identified and analysed over the years, as mirrored in the current recommendations of the European Hernia Society, but some misconceptions still remain that hinder wide implementation. Method: A literature search was performed in the PubMed and GoogleScholar databases on 15 July 2021 and additionally on 30 March 2022 to include recent updates. The goal was to describe the scientific background behind the optimal strategies for reducing incisional hernia risk after closure of abdominal wall incisions in a narrative style review Results: An aponeurosis alone, small bites/small steps continuous suture technique should be used, using a slowly resorbable USP 2/0 or alternatively USP 0 suture loaded in a small ½ circle needle. The fascial edges should be properly visualised and tension should be moderate. Conclusion: Despite the reproducibility, low risk and effectiveness in reducing wound complications following abdominal wall incisions, utilisation of the recommendation of the guidelines of the European Hernia Society remain relatively limited. More work is needed to clear misconceptions and disseminate the established knowledge and technique especially to younger surgeons